2002
DOI: 10.1002/app.10851
|View full text |Cite
|
Sign up to set email alerts
|

A novel way of enhancing the electrical and thermal stability of conductive epoxy resin–carbon black composites via the Joule heating effect for heating‐element applications

Abstract: ABSTRACT:The influence of Joule heating treatments and carbon black (CB) on the electrical and thermal behavior of epoxy resin composites is well described in this article. The effect of CB and Joule heating on network structure characteristics, such as shrinkability, interparticle distance between conductive particles, crosslinking density, hardness, thermoelectric power, thermal conductivity, the thermal expansion coefficient, and scanning electron microscopy, of epoxy composites was investigated. The electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 15 publications
(67 reference statements)
3
52
0
Order By: Relevance
“…Since polymers are, in general, insulating materials, many efforts have been directed to improve their electrical conductivity [1,2,3]. Electrically insulating polymers such as polyurethane can be specifically modified in order to increase its conductivity by dispersing conductive fillers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Since polymers are, in general, insulating materials, many efforts have been directed to improve their electrical conductivity [1,2,3]. Electrically insulating polymers such as polyurethane can be specifically modified in order to increase its conductivity by dispersing conductive fillers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…22 Particularly, since the gap distance between filler aggregates critically depends on u, it is expected that the amplitude of Joule heat induced resistance relaxation also exhibits marked concentration dependence. As shown in Figure 2(a), PMVS/CB composite containing 9.1 vol % CB shows more obvious resistance decrease than that containing 13.1 vol % CB because the closer to the percolation threshold the farther away from perfect is the percolation network and therefore more fragile.…”
Section: Percolation Transitionmentioning
confidence: 99%
“…The PTC effect strongly depends on the time related thermal history, 19,20 so that thermal aging is becoming a common method to eliminate the thermal history and to stabilize the conduction behavior. 21,22 Tao et al 23 and Park et al 24 found that annealing at temperatures below and above T m has different influences on the redistribution of filler aggregates in the matrix and also on the PTC/NTC behavior of CPCs. Their observations were confirmed by Song and Zheng,20 and were explained with respect to the breakdown and reformation of the percolation network at lower temperatures, as well as the agglomeration of carbon black (CB) aggregates and formation of percolation network in the melts.…”
Section: Introductionmentioning
confidence: 98%
“…1,2 The increasing requests for thermistors, temperature controllers, self-heaters, gas sensors, electrostatic charge dissipation, and electromagnetic interference (EMI) shielding are pushing many researchers to explore new concepts and related materials. [3][4][5][6][7][8][9][10] Electrically conductive polymer composites (CPCs) are obtained by the blending of an insulating polymer matrix with conductive fillers such as carbon black, carbon fibers, and graphite or metal particles.…”
Section: Introductionmentioning
confidence: 99%